2012
DOI: 10.1186/1752-153x-6-61
|View full text |Cite
|
Sign up to set email alerts
|

Green tea increases the survival yield of Bifidobacteria in simulated gastrointestinal environment and during refrigerated conditions

Abstract: BackgroundThe well–known prebiotics are carbohydrates but their effects may not always be beneficial, as they can also encourage the growth of non-probiotic bacteria such as Eubacterium biforme and Clostridium perfringens. Therefore, new alternatives such as non-carbohydrate sources to stimulate the growth of probiotics are needed. The aim of this work was to evaluate (I) the green tea polyphenols by HPLC-LC/MS and (II) the protective effect of green tea extract on viability and stability of B. infantis ATCC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…For example, ultrasound-assisted extraction (UAE) [31,32] represents a novel and low-cost technique that can improve the bioactive compound extraction rate and efficiency. UAE can be applied for both the extraction of interest compounds and for their encapsulation by different biopolymers [33][34][35][36][37]. There are different thermal processes (e.g., steaming, pressured steam-heating, drum drying, roasting, and microwave heating), largely applied to increase the palatability, stability, and safety of cereal-based food products.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ultrasound-assisted extraction (UAE) [31,32] represents a novel and low-cost technique that can improve the bioactive compound extraction rate and efficiency. UAE can be applied for both the extraction of interest compounds and for their encapsulation by different biopolymers [33][34][35][36][37]. There are different thermal processes (e.g., steaming, pressured steam-heating, drum drying, roasting, and microwave heating), largely applied to increase the palatability, stability, and safety of cereal-based food products.…”
Section: Introductionmentioning
confidence: 99%
“…These carbohydrate-type prebiotics may however non-specifically encourage the growth of all gut organisms, including the non-probiotic pathogenic bacteria. Therefore, newer alternatives of non-carbohydrate origin need to be explored for stimulation of probiotic flora [5]. …”
Section: Introductionmentioning
confidence: 99%
“…). Vodnar and Socaciu () reported that green tea improves the survival of Bifidobacteria in a simulated gastrointestinal environment, while HC Lee et al . () in an in vitro study found that tea phenolics reduced the growth of pathogenic bacteria, with commensal bacteria being less affected.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from animal studies and in vitro work indicating that tea has pre-biotic effects. Molan et al (2010); Axling et al (2012); Vodnar and Socaciu (2012); HC Key: MRSA, methicillin-resistant Staphylococcus aureus; RCS, randomised crossover studies.…”
Section: Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation